Corporate governance and valuation of GLCs in Singapore. - Kong, Melvin Chia Ming. (2008)
On 12 May 2000, Singapore Telecommunication failed in its second attempt to acquire a strategic stake in foreign counterparts. This invoked an intriguing debate on whether the Singapore Government should divest its stakes in the Government Linked Companies (GLCs) and how fast. Generating a corporate governance and transparency index under the guidelines from Disclosure and Accounting Standard Committee and undertaking regression studies and event studies, we set out to investigate the relationship between government involvement, corporate governance, transparency and the value of the firm. Results show that in the short run, higher transparency is detrimental to firm value. We also find strong relationship between corporate governance, government involvement and firm value though the results are inconclusive by empirical studies. However, we propose that government involvement, higher corporate governance and transparency add value to firms due to non-quantitative benefits that they provide. Several recommend